INFLUENCE OF THE TIMELINESS OF PRODUCT DELIVERY ON CUSTOMER SATISFACTION AT CV. EAST JAYA SUMEDANG ELECTRONICS - Dini, Erti (Journal of Economic Empowerment Strategy (JEES), 2024)
CV Timur Jaya Elektronik is a company operating in the industrial sector that sells various kinds of electronic goods such as televisions, refrigerators, air conditioners and other electrical equipment. Based on the research results, it shows that there are problems caused by the timeliness of product delivery on consumer satisfaction. The purpose of this research is to determine the effect of product delivery time on consumer satisfaction at CV. Timur Jaya Electronics Sumedang. This research uses a descriptive method with a quantitative approach. Data collection techniques in this research are observation, interviews and distributing questionnaires. The data analysis techniques that will be tested are validity test, reliability test, simple linear regression, Spearman rank correlation coefficient, coefficient of determination and t test. Based on the research results, it shows that there is a positive influence between the timeliness of product delivery on consumer satisfaction according to a simple linear regression test, while according to the Spearman Rank correlation the influence of timeliness of product delivery on consumer satisfaction is strong and based on the results of the coefficient of determination of timeliness of product delivery on consumer satisfaction in CV. Timur Jaya Elektronik Sumedang has a positive and significant influence and the rest is influenced by other factors. The suggestion that researchers can put forward is to be more thorough in providing product delivery information to consumers, so that there are no misunderstandings between companies and consumers. As well as providing the right delivery time